149k views
5 votes
Let $f(x) = 2x^2 + 3x - 9,$ $g(x) = 5x + 11,$ and $h(x) = -3x^2 + 1.$ Find $f(x) - g(x) + h(x).$

Let $f(x) = 4x - 7$, $g(x) = (x + 1)^2$, and $s(x) = f(x) + g(x)$. What is $s(3)$?

Let $f(x) = 3x + 2$ and $g(x) = x^2 - 5x - 1.$ Find $f(g(x)).$

Let $f(x) = 3(x - 6)^2 + 1$. What is the range of $f$? Express your answer with interval notation.

User JohnnyM
by
6.0k points

1 Answer

4 votes

QUESTION 1

Given that:


f(x)=2x^2+3x-9,


g(x)=5x+11,

and


h(x)=-3x^2+1

Then;


f(x)-g(x)+h(x)=2x^2+3x-9-(5x+11)+(-3x^2+1)


f(x)-g(x)+h(x)=2x^2+3x-9-5x-11-3x^2+1

Group similar terms;


f(x)-g(x)+h(x)=2x^2-3x^2+3x-5x-11-9+1

Simplify;


f(x)-g(x)+h(x)=-x^2-2x-19

QUESTION 2

Given that;


f(x)=4x-7.


g(x)=(x+1)^2

and


s(x)=f(x)+g(x)

Substitute the functions;


s(x)=4x-7+(x+1)^2

Substitute x=3


s(3)=4(3)-7+(3+1)^2


s(3)=12-7+(4)^2


s(3)=5+16


s(3)=21

QUESTION 3

Given:


f(x)=3x+2


g(x)=x^2-5x-1


f(g(x))=f(x^2-5x-1)

This implies that;


f(g(x))=3(x^2-5x-1)+2

Expand the parenthesis;


f(g(x))=3x^2-15x-3+2


f(g(x))=3x^2-15x-1

QUESTION 4

The given function is;


f(x)=3(x-6)^2+1

Let


y=3(x-6)^2+1


\Rightarrow y-1=3(x-6)^2


\Rightarrow (y-1)/(3)=(x-6)^2


\Rightarrow \sqrt{(y-1)/(3)}=x-6


\Rightarrow x=6+\sqrt{(y-1)/(3)}

The range is:


(y-1)/(3)\ge0


y-1\ge0


y\ge1

The interval notation is;


[1,+\infty)

User Harish Vangavolu
by
6.1k points